ANALISIS KEMAMPUAN METAKOGNITIF MAHASISWA PGSD DALAM PEMBELAJARAN IPS - Rizki Ananda; Ebi Nursyalila; Nila Wahyuni; Muhammad Aghu Fahri Azmi; Viola Parisha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the metacognitive abilities of students in the Elementary School Teacher Education (PGSD) study program of FKIP Universitas Pahlawan Tuanku Tambusai in Social Studies (IPS) learning. Metacognition is a critical component in higher education as it relates to students’ self-awareness and self-regulation of their own cognitive activities. This study employed a descriptive quantitative approach involving 60 fourth-semester PGSD students. Data were collected using an adapted Metacognitive Awareness Inventory (MAI) questionnaire (Schraw & Dennison, 1994) consisting of 52 items on a 5-point Likert scale. Data were analyzed using descriptive statistics. The results show that PGSD students’ metacognitive abilities are overall in the moderate category with a mean score of 66.95. The declarative knowledge component received the highest score (72.4), while the evaluation component obtained the lowest score (61.5). These findings indicate the need to develop IPS learning strategies that explicitly facilitate the development of students’ monitoring and evaluation abilities. Implications of this study are expected to be the basis for curriculum development and learning strategies that support the improvement of PGSD students’ metacognitive abilities.